Bone grafts in sports traumatology - Francavilla, V. C.; Triolo, V.; Sutera, R.; Quattrocchi, A.; Iovane, A.; Francavilla, G. (Medicina dello Sport, 2011)
The purpose of this paper is to verify whether the enormous advances that are spoken of in the field of bone grafts, micro-surgery and tissue engineering really do exist and whether they can be used in sports traumatology to obtain faster cure, but above all to obtain, in the field of previously untreatable bone lesion repair, an acceptable consolidation with a good revival of physical activity. In this trial we briefly describe the different types of grafts with their respective advantages and disadvantages; an analysis is then presented of the effectiveness of grafts in 9 sporting patients suffering from injuries with loss of bone substance and assessed 3, 6 and 9 months after the operation.